Sustainable Diplomacy : Expanding the Potential of Diplomatic Relations (Lessons from the Netherlands) - Dostal, Pavel; Druláková, Radka, 1973-; Trávníčková, Zuzana, 1977-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
Within its scope, the thesis theoretically underpins the concept of sustainable diplomacy, using an evolutionary approach to diplomacy, and introduces criteria that allow its application on exemplary Dutch foreign policy projects. Three Dutch sustainable diplomacy projects are analyzed using a unified framework to allow their comparison and evaluation based on the criteria from the theoretical part. In light of the findings of the analysis, the thesis also acknowledges limitations of sustainable diplomacy encountered during the research to provide foundations for future development of the concept.
Vedoucí práce: Radka Druláková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses